Molecular Mass and Localization of α-1,3-Glucan in Cell Wall Control the Degree of Hyphal Aggregation in Liquid Culture of Aspergillus nidulans - Miyazawa, Ken; Yoshimi, Akira; Kasahara, Shin; Sugahara, Asumi; Koizumi, Ami; Yano, Shigekazu; Kimura, Satoshi; Iwata, Tadahisa; Sano, Motoaki; Abe, Keietsu (Frontiers in Microbiology, 2018)
α-1,3-Glucan is one of the main polysaccharides in the cell wall of filamentous fungi. Aspergillus nidulans has two α-1,3-glucan synthase genes, agsA and agsB. We previously revealed that AgsB is a major α-1,3-glucan synthase in vegetative hyphae, but the function of AgsA remained unknown because of its low expression level and lack of phenotypic alteration upon gene disruption. To clarify the role of α-1,3-glucan in hyphal aggregation, we constructed strains overexpressing agsA (agsAOE) or agsB (agsBOE), in which the other α-1,3-glucan synthase gene was disrupted. In liquid culture, the wild-type and agsBOE strains formed tightly aggregated hyphal pellets, whereas agsAOE hyphae aggregated weakly. We analyzed the chemical properties of cell wall α-1,3-glucan from the agsAOE and agsBOE strains. The peak molecular mass of α-1,3-glucan from the agsAOE strain (1,480 ± 80 kDa) was much larger than that from the wild type (147 ± 52 kDa) and agsBOE (372 ± 47 kDa); however, the peak molecular mass of repeating subunits in α-1,3-glucan was almost the same (after Smith degradation: agsAOE, 41.6 ± 5.8 kDa; agsBOE, 38.3 ± 3.0 kDa). We also analyzed localization of α-1,3-glucan in the cell wall of the two strains by fluorescent labeling with α-1,3-glucan-binding domain–fused GFP (AGBD-GFP). α-1,3-Glucan of the agsBOE cells was clearly located in the outermost layer, whereas weak labeling was detected in the agsAOE cells. However, the agsAOE cells treated with β-1,3-glucanase were clearly labeled with AGBD-GFP. These observations suggest that β-1,3-glucan covered most of α-1,3-glucan synthesized by AgsA, although a small amount of α-1,3-glucan was still present in the outer layer. We also constructed a strain with disruption of the amyG gene, which encodes an intracellular α-amylase that synthesizes α-1,4-glucooligosaccharide as a primer for α-1,3-glucan biosynthesis. In this strain, the hyphal pellets and peak molecular mass of α-1,3-glucan (94.5 ± 1.4 kDa) were smaller than in the wild-type strain, and α-1,3-glucan was still labeled with AGBD-GFP in the outermost layer. Overall, these results suggest that hyphal pellet formation depends on the molecular mass and spatial localization of α-1,3-glucan as well as the amount of α-1,3-glucan in the cell wall of A. nidulans.